Управлінська готовність та управлінська компетентність як важлива складова професійної пдготовки фахівців оперативно-рятувальної служби цивільного захисту - Панімаш, Юлія (Східноєвропейський національний університет імені Лесі Українки, 2018)
У статті проведено ґрунтовний аналіз психолого-педагогічної літератури проблеми дослідження. Розкрито сутність поняття професійна підготовка фахівців цивільного захисту, управлінська готовність та управлінська компетентність. Встановлено відмінність «управлінської компетентності» та «готовності до управлінської діяльності». Доведено прямий зв’язок готовності до управлінської діяльності й управлінської компетентності. Визначено, що формування управлінської компетентності є наслідком управлінської готовності.In the article a tho rough analysis of the problem of research isconducted in the psychological and pedagogical literature. The essence of the conceptis the vocational training of specialist sin civildefense managerialreadinessandmanagerialcompetence. Thereis a distinctionbetween "managerialcompetence" and "readinessformanagementactivity". Directconnectionofreadinessformanagementactivityandmanagerialcompetencehas beenproved. Itisdeterminedthattheformationofmanagerialcompetenceis a consequenceofmanagerialreadiness. Having conducted a thorough analysis of the psychological and pedagogical literature, the problem of the study made it possible to establish that the formation of readiness for management activity is a necessary condition for the professional training of the personnel of the personnel of the civil protection service. Readiness for the management of future specialists of the Rescue Service of Civil Protection is defined as a complex integrated personality education, which is the result of professional training and is manifested in the degree of formation of knowledge, skills, skills, motives and values of cadets, their managerial qualities (organizational, leadership, communicative, socially significant), which cause rapid adaptation to the fulfillment of official duties in emergency situations and the successful professional activity of fire and rescue p. sections. Direct connection of readiness for management activity and managerial competence has been proved. It is determined that the formation of readiness for management activity is the first step in mastering the managerial competence, which is characterized by the long-term development of life-long development, and the availability of certain work experience.
Keywords: професійна підготовка фахівців цивільного захисту; управлінська діяільність; управлінська компетентність